Empowerment in Adolescent Patients with a Disability/Chronic Condition: A Scoping Review - Kennedy Austin; Carly Pistawka; Colin J. D. Ross; Kathryn A. Selby; Alice Virani; Vanessa Kitchin; Alison M. Elliott (Children)
Background/Objectives: Empowerment has been associated with several positive outcomes in healthcare; however, there is limited insight on empowerment levels within the adolescent population of those with a chronic condition/disability. The aim of this scoping review was to identify gaps in the existing literature on empowerment levels within this population. Methods: Five databases (MEDLINE [Ovid], EMBASE [Ovid], PsycINFO [Ebsco], CINHAL [Ebsco] and Web of Science [UBC]) and grey literature were searched. Results: A total of 67 studies were included and used for data extraction including descriptive numerical analysis followed by a narrative review. Extracted data were divided into demographic characteristics (e.g., ethnicity/ancestry), type of disability/condition (e.g., type 1 diabetes), interventions used to increase empowerment or empowerment-adjacent elements, quantitative and qualitative tools used to measure empowerment (e.g., questionnaires and/or interviews), domains/outcomes associated with empowerment (e.g., self-control), and review articles. Several interventions were shown to have positive effects on empowerment levels in adolescents with a chronic condition/disability. Conclusions: Gaps were identified in the consideration of ethnicity/ancestry and socioeconomic status, demonstrating a need for future research in this space to focus on the intersection of disability, ethnicity/ancestry, and socio-economic status and the implementation of interventions promoting empowerment.